High frequency of horizontal transfer in Jockey families (LINE order) of drosophilids - Tambones, Izabella L. [UNESP]; Haudry, Annabelle; Simão, Maryanna C. [UNESP]; Carareto, Claudia M. A. [UNESP] (Springer Nature, 2019)
Background: The use of large-scale genomic analyses has resulted in an improvement of transposable element sampling and a significant increase in the number of reported HTT (horizontal transfer of transposable elements) events by expanding the sampling of transposable element sequences in general and of specific families of these elements in particular, which were previously poorly sampled. In this study, we investigated the occurrence of HTT events in a group of elements that, until recently, were uncommon among the HTT records in Drosophila - the Jockey elements, members of the LINE (long interspersed nuclear element) order of non-LTR (long terminal repeat) retrotransposons. The sequences of 111 Jockey families deposited in Repbase that met the criteria of the analysis were used to identify Jockey sequences in 48 genomes of Drosophilidae (genus Drosophila, subgenus Sophophora: melanogaster, obscura and willistoni groups; subgenus Drosophila: immigrans, melanica, repleta, robusta, virilis and grimshawi groups; subgenus Dorsilopha: busckii group; genus/subgenus Zaprionus and genus Scaptodrosophila). Results: Phylogenetic analyses revealed 72 Jockey families in 41 genomes. Combined analyses revealed 15 potential HTT events between species belonging to different genera and species groups of Drosophilidae, providing evidence for the flow of genetic material favoured by the spatio-temporal sharing of these species present in the Palaeartic or Afrotropical region. Conclusions: Our results provide phylogenetic, biogeographic and temporal evidence of horizontal transfers of the Jockey elements, increase the number of rare records of HTT in specific families of LINE elements, increase the number of known occurrences of these events, and enable a broad understanding of the evolutionary dynamics of these elements and the host species.
Keywords: Drosophila; HTT; Scaptodrosophila; transposable elements; VHICA; Zaprionus